Analysis and description of the different realities of the Program Local Agents innovation - RN - Silva, Napiê Galvê Araujo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The article seeks to carry out an assessment and characterization Agents Program Innovation Locations - ALI, Sebrae-RN, from a comparative analysis of peculiarities, specificity and uniqueness of the challenges faced by the agents, given the territorial dispersion of all attended companies for each agent, and the monitoring, evolution, and innovation management in companies in all industries and sectors of the economy, among other unique features specific only experienced by in the state agents compared the blessings of the implementation of the said actually program the great Christmas, as a result of the business conglomerate in the same perimeter. The methodology used was the application of semi-structured questionnaire with closed multiple choice questions along with 18 agents working in seven regional offices of Sebrae-RN in the state. Such research can prove that the monitoring for each of the state agent, have degrees greater difficulties due to the spatial dispersion of their accompanied companies as well as the diversity of segments and sectors given the lack of similar projects in the same municipality.